Synergistically improving the thermoelectric and mechanical performance for p-type MnGe1−xSbxTe2 alloys. Issue 16 (7th April 2022) - Gao, Lei; Dong, Ximeng; Zheng, Shuqi; Li, Wenhao; Yang, Xinyue
Abstract : A high TE performance GeMnTe2 -based material with improved thermoelectric and mechanical properties is obtained by Sb doping. Excellent power factors could be achieved in the tested temperature range. Abstract : The MnGeTe2 compound crystallizes in a cubic structure without any phase transition and has great potential for enhancing the thermoelectric merit of MnGeTe2 -based materials. In this work, Sb was used as an effective dopant to replace Ge sites in MnGeTe2 compounds. By optimizing the carrier concentration, excellent power factors can be obtained in the tested temperature range. Meanwhile, the characterization results show that Sb doping introduces point defects and induces grain refinement, which enhances phonon scattering and improves thermoelectric transport performance by reducing lattice thermal conductivity. Eventually, the ZT value increases from ∼0.65 for pure phase MnGeTe2 to ∼0.84 for MnGe0.90 Sb0.1 Te2 at 717 K by synergistic regulation of the electrical and thermal conductivities. In addition, the hardness test results of the samples show that the doping of Sb endows the MnGeTe2 -based thermoelectric material with a higher Vickers hardness (>200 HV ) and shows favorable mechanical properties.